Comparing Experiences of Women Who Were Direct Breastfeeding and Women Who Used Expressed Breast Milk to Feed Their Infants. Issue 2 (March 2023) - Anders, Lisa A.; Robinson, Karen; Ohlendorf, Jennifer M.; Hanson, Lisa
Abstract: Purpose: To provide understanding about feeding experiences of women who provide breast milk through direct breastfeeding and exclusive expression and to compare these experiences. Study Design and Methods: A qualitative study was conducted to gather experiences from the perspectives of women who had given birth to a healthy, term infant within the past 12 months and exclusively fed breast milk for at least 2 weeks. The sample was recruited from motherhood and breastfeeding support groups on Facebook. Groups had state- or national-based memberships. Interviews were examined for themes that were compared between feeding groups using thematic analysis. Results: Fifteen new mothers participated. Under the primary themes of Similarities and Differences, seven subthemes were identified: Fatigue, Importance of Support, Finding Joy in a Common Goal, Mixed Feelings, Trusting versus Tracking, Latching versus Body Failure, and Pumping in Isolation . Clinical Implications: Mothers who provide breast milk share common experiences and feelings of satisfaction. Expressed breast milk feeding offers some mothers a way to provide the benefits of breast milk while preserving a balance between maternal and infant physical and mental health needs. Understanding the different ways in which women manage breast milk feeding while balancing maternal and infant needs can prepare nurses to discuss various methods of breast milk feeding and provide individualized support. Abstract : In this qualitative study, 15 women shared their personal accounts of breast milk feeding. Mothers who provide breast milk share common experiences and feelings of satisfaction. Expressed breast milk feeding offers some women a way to provide the benefits of breast milk while preserving a balance between maternal and infant physical and mental health needs. Understanding the different ways in which women manage breast milk feeding while balancing maternal and infant needs can prepare nurses to discuss various methods of breast milk feeding and provide individualized support.